2018
DOI: 10.21068/c2018.v19s1a12
|View full text |Cite
|
Sign up to set email alerts
|

Una nueva rana nodriza de los bosques de niebla asociados a la cuenca del Orinoco de Colombia

Abstract: Se describe una nueva especie de rana nodriza proveniente de las estribaciones andinas en el departamento de Boyacá y asociada a la cuenca del río Orinoco en Colombia. Esta especie posee una similitud morfológica con Hyloxalus picachos que habita en las estribaciones andinas en el departamento de Caquetá, pero difiere de esta porque la banda lateral oblicua se extiende hasta el rostro y por su patrón cromático del iris en vida. Se describe el cambio ontogénico de sus estados larvales junto con sus vocalizacion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Our analyses showed that several specimens misidentified as Scinax x-signatus were S. eurydice, S. ruber, S. similis , or S. fuscovarius . Several specimens from Colombia and central-west Venezuela to which the name S. x-signatus has been applied (Rivero, 1969; Gorzula and Señaris, 1999; Acosta-Galvis, 2000; Lynch, 2006b; Ugueto and Rivas-Fuenmayor, 2010) belong to a distinct lineage that is only distantly related to S. x-signatus . That lineage here named Scinax sp.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses showed that several specimens misidentified as Scinax x-signatus were S. eurydice, S. ruber, S. similis , or S. fuscovarius . Several specimens from Colombia and central-west Venezuela to which the name S. x-signatus has been applied (Rivero, 1969; Gorzula and Señaris, 1999; Acosta-Galvis, 2000; Lynch, 2006b; Ugueto and Rivas-Fuenmayor, 2010) belong to a distinct lineage that is only distantly related to S. x-signatus . That lineage here named Scinax sp.…”
Section: Discussionmentioning
confidence: 99%
“…Advertisement calls have been described for 24 of the 61 described species of Hyloxalus, including H. abditaurantius (Silverstone, 1975) (Grant and Castro, 1998), H. arliensis (Acosta-Galvis et al, 2020), H. awa (Coloma, 1995), H. azureiventris (Lötters and Kneller, 2000), H. bocagei Jiménez de la Espada, 1870 (Páez-Vacas et al, 2010), H. elachyhistus (Edwards, 1971) (Koch et al, 2011), H. fascianigrus (Grant and Castro, 1998), H. felixcoperari Acosta-Galvis and Vargas-Ramírez, 2018, H. italoi Páez-Vacas et al, 2010, H. jacobuspetersi (Coloma, 1995), H. maculosus (Rivero, 1991) (Páez-Vacas et al, 2010), H. mystax (Duellman and Simmons, 1988) (Almendáriz and Batallas, 2011), H. nexipus (Frost, 1986) (Coloma, 1995), H. patitae (Lötters et al, 2003b), H. pulchellus (Coloma, 1995), H. sanctamariensis Acosta-Galvis and Pinzón, 2018, H. sauli (Edwards, 1974) (Páez-Vacas et al, 2010), H. subpunctatus (Cope, 1899) (Fandiño et al, 1997; Navas and Bevier, 2001), H. toachi (Coloma, 1995) (Quiguango-Ubillús and Coloma, 2008), H. vergeli Hellmich, 1940 (Mendoza-Henao et al, 2022), H. vertebralis (Coloma, 1995), and H. yasuni Páez-Vacas et al, 2010.…”
Section: Methodsmentioning
confidence: 99%
“…In Colombia, the genus comprises 26 species, with the highest species richness found in Andean cloud forests, where 23 species are distributed (Acosta-Galvis et al, 2020; Anganoy-Criollo et al, 2022). Among these, 13 species have been reported in the Cordillera Oriental, 11 in the Cordillera Central (including the Colombian Massif), and 6 species in the Cordillera Occidental (Acosta-Galvis and Pinzón, 2018; Acosta-Galvis and Vargas-Ramírez, 2018; Acosta-Galvis et al, 2020; Anganoy-Criollo et al, 2022). Most of these species inhabit moderate elevations (16 species within the elevational range of 1,000–2,000 m) and the lowest diversity occurs at elevations above 3,000 m (2 species; Bernal and Lynch, 2008; Acosta-Galvis et al, 2020; Anganoy-Criollo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) A deep search on the digital repositories of the Instituto de Investigación de Recursos Biológicos Alexander von Humboldt -IAvH (2019) (until 2021) and the book series "Colombia Diversidad Biótica" (Rangel-Ch, 2019). 5) We consolidate a taxonomic list of Páramo species reported in the scientific literature (Acosta-Galvis, 2000, Ardila-Robayo & Acosta-Galvis, 2000Lynch & Suárez, 2002;Bernal & Lynch, 2008;Acosta-Galvis, 2015;Buitrago-González et al, 2016;Meza-Joya & Torres, 2016) We generated a database and manually removed duplicates for a total of 882 documents. For each of these documents, the abstract, methods, study area, results, and supplementary material were read following the PRISMA protocol (Liberati et al, 2009;Shamseer et al, 2015), to ensure that all eligible documents met at least one of the following inclusion criteria: 1) It includes studies in ecosystems above 2700 m in Colombia; 2) It presents data on species reported in the taxonomic list compiled from the scientific literature (search strategy 5), and available records (search strategy 6); and 3) Study areas coincide spatially with some Páramo complex.…”
Section: Methodsmentioning
confidence: 99%